Penggunaan Pupuk Kandang pada Padang Rumput di Lahan Kering Sulawesi Tenggara - Harapin Hafid H; . Darwis; M Jaya (Faculty of Animal Science, Bogor Agricultural University, 2007)
Generally, the permanent pasture of dry farming in South East Sulawesi is dominated by the perennial grass and coppi plant, which have very low palatability and benefit for livestock. The aim of the research was to increase the productivity of pasture in South East Sulawesi by introducing perennial grasses and manure application. The experiment was conducted in UPTD and analytical laboratory of FMIPA from April to September 2006 using three types of perennial grasses i.e. Brachiaria decumbens, Paspalum dilatatum and Cynodon plectostachyrus. Perception conducted to calculate the botanical composition and soil properties before and after the treatment. The field experiment was carried out as two factorial experiment arranged in Randomized Block Design. The first factor was the species of perennial grass and the second factor was different level of manure fertilizer. The result of the experiment showed that the crude fibre content of B. decumbens was lower than those of P. dilatatum and C. plectostachyrus. The crude fibre content increased with the increasing manure application. But the protein content of B. decumbens was higher than those of P. dilatatum and C. plectostachyrus. It is suggested to plant B. decumbens to get higher quality forage for livestock in South East Sulawesi. Key words: manure, perennial grass, pasture, protein, fiber